Hepatorenal Syndrome pada Pasien Sirosis: Tinjauan Pustaka - Sulystio, Lenny (PT Kalbe Farma Tbk., 2025)
Hepatorenal syndrome (HRS) is a serious renal complication that frequently develops in patients with decompensated cirrhosis, causes systemic circulatory disturbance. HRS involves complex pathogenesis mechanisms and treatment. Various therapies have been developed to tackle HRS, such as the use of vasoconstrictor agents, intravenous albumin, transjugular intrahepatic portosystemic shunting (TIPS), and liver transplantation.